Re-thinking Legal and Policy Environment in the Mining Sector Thirty Years after Execution of Economic Reforms in Tanzania - Mikidadi, Muhanga (Journal of Policy and Leadership, 2018)
This article examines legal and policy environments in the mining sector after the economic reforms in Tanzania, it specifically: analyses the sector before the reforms, examines the legal and policy responses after the economic reforms; and profiles how those policies and legislations have impacted the socio-economic and political aspects related to mining in Tanzania. A documentary review (documentary research method) was used in collecting relevant information. It was revealed that prior to the reforms the extent of minerals extraction in Tanzania was low compared after the reforms, with the mineral sector development operations largely state owned and run by government enterprises. The legal and policy responses examined include the Mineral Policy of 1997, Mineral Act of 1998, Mining Act of 2010, New Investment Policy and the Tanzania Investment Act No. 26 of 1997, Mining (Environmental Management and Protection) Regulations of 1999, Natural Wealth and Resources (Permanent Sovereignty) Act, 2017; Natural Wealth and Resources Contracts (Review and Re-Negotiation of Unconscionable Terms) Act, 2017, the Written Laws (Miscellaneous Amendments) Act 2017; Extractive Industry Transparency and Accountability Act, 2015 and The Finance Act of 2017. These legal and policy responses in the mining sector were found to have both positive and negative impacts. It has been observed that the reforms in the sector have not fully captured the expectations of Tanzanians. The article ends up by suggesting several recommendations